Order of the Sanguines: Blood Infernal - Book 5 Book 3 - Rollins, James, 1961-; Cantrell, Rebecca (New York : William Morrow,an imprint of HarperCollins Publishers, 2015.)
"The third installment in the bestselling gothic series, about an ancient order who speak the truth behind Christs miracles and strive to protect the world from evil from New York Times bestselling authors James Rollins and Rebecca Cantrell"--
Keywords: Jesus Christ -- Miracles; Fiction; Bible. -- History of Biblical events; Fiction; Archaeologists -- Fiction; Good and evil -- Fiction; Christian sects -- Fiction